Charles Taylor: un hegelian fără un hegelianism al negativității? (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article examines Charles Taylor’s interpretation of Hegel’s philosophy of recognition and evaluates its contribution to contemporary debates on identity, multiculturalism, and nationalism. It argues that, although Taylor successfully emphasizes recognition, authenticity, and dialogue, his interpretation remains incomplete because it neglects the dialectical role of conflict, negativity, and material historical conditions. The article concludes that a fuller Hegelian perspective requires greater attention to historical change, political struggle, and the socio-economic context shaping contemporary demands for recognition. This abstract is generated with artificial intelligence.